Knowledge and Learning in Complex Urban Renewal Projects; Towards a Process Design - Janneke Bemmel Van (European Regional Science Association (ERSA), 2006)
Urban Renewal is carried out to renovate, demolish and rebuild houses in problematic urban areas. Urban renewal processes are complex; many actors are involved, the goals and strategies of these actors can change over time, and contextual factors (such as the housing market, residents' wishes, the political direction) change constantly. This creates a lot of uncertainty in urban renewal processes; uncertainty about knowledge and values (substantive uncertainty), uncertainty about the intentions and strategies of the parties involved (strategic uncertainty), and uncertainty about when, where and by whom decisions are made (institutional uncertainty). With learning, this uncertainty can be made more manageable. The creation, sharing, use and evaluation of knowledge in urban renewal networks helps to respond to changes in, amongst others, residents' wishes, the housing market, and technological developments. Learning can be defined as the creation of knowledge that is applicable in the activities of the parties involved. In urban renewal, four important steps towards learning can be recognised: the (collective) development of knowledge, the mutual sharing of knowledge, the use of the relevant knowledge available, and the evaluation of the knowledge gathered. A complex urban renewal project has been studied in the second largest Dutch city; Rotterdam, in the district 'Hoogvliet'. This case study, that has an explorative character, exists of interviews with professionals working on urban renewal in Hoogvliet and observations during meetings at several levels of the cooperation network. Preliminary findings suggest that the development and sharing of knowledge in urban renewal in Hoogvliet takes place mainly through face-to-face contact, for instance during meetings and debates, and not so much in writing, for instance in databases or guidebooks. Another finding is that for collective learning to occur, a minimum of collective knowledge is needed; the parties involved must know the basics of the tasks and responsibilities of the other parties and of the knowledge built up earlier in the process. Furthermore, to increase the potential for learning, it seems smarter to sketch the outlines of complex long-term projects and concretize these along the way, then to make detailed plans far in advance.
Keywords: 330